Night of the hawk - Brown, Dale, 1956- (New York : Berkley Books, 1993)
Story of the crew of the "Old Dog," a high tech B-52 bomber, and First Lieutenant Daviet Luger who has become one of the KGB.
Library Journal
Publisher's Weekly
Wilson's Fiction
Adult.
Adult
Keywords: United States. -- Air Force -- Fiction; United States. -- Air Force -- Fiction; Bombers -- Fiction; Stealth aircraft -- Fiction; Bombers -- Fiction; Espionage -- Fiction; Spies -- Fiction; Stealth aircraft -- Fiction; Lithuania -- Fiction; Lithuania -- Fiction; Adventure stories; Spy stories